Proximate ferromagnetic state in the Kitaev model material α-RuCl3 - H. Suzuki (Nature Portfolio, 2021)
RuCl3 has stood out as a prime candidate in the search for quantum spin liquids; however, its antiferromagnetic ordering at low temperature suggests deviations from typical QSL models. Here, using resonant inelastic x-ray scattering, the authors provide a comprehensive determination of the low energy effective Hamiltonian.